TAFSIR AYAT-AYAT SOSIAL KEMASYARAKATAN DALAM AL-QURAN - Zabidi, Ahmad (JURNAL ILMIAH FALSAFAH: Jurnal Kajian Filsafat, Teologi dan Humaniora, 2020)
The purpose of this research is to describe the interpretation of social verses in the Koran. The method used in this research is a qualitative method with the type of research library research (literature review), while the technical data analysis uses content analysis (content analysis). The results of this study indicate that the foundation of legal and social justice is faith, which is essentially stated in the two sentences of the creed. Deliberation has deep potential in the life of Islamic society which is not just a political system of government. Deliberation is the basic character of the whole society. All issues are based on deliberation. Ukhuwah is defined as "every equality and harmony with other parties, be it the equality of descent in terms of mother, father or both as well as from the aspect of breastfeeding, this brotherhood is that love, peace, cooperation and unity should be the main foundation of the Muslim community. Tolerance is the attitude of letting people have other beliefs and accepting that statement because it recognizes the right to freedom of everyone in terms of their own beliefs. Meanwhile, gender is a trait inherent in both men and women that is formed socially and culturally with the result of the establishment of social relationships that differentiate the functions, roles and responsibilities of the two sexes.